2018
DOI: 10.1007/s12020-018-1693-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of cooled and uncooled microwave ablation for the treatment of benign thyroid nodules: a systematic review and meta-analysis

Abstract: MWA is an effective treatment modality for BTNs. When considering the patient's comfort, cMWA would be a more preferable procedure with less complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 51 publications
4
42
2
Order By: Relevance
“…MWA is a new local thermal ablation technique that has a fast heating speed, strong coagulation ability, and a large ablation zone, so this technique has become a major method in heat ablation therapy. It is an effective treatment of thyroid nodules worldwide (8)(9)(10)(11). We found that intracystic hemorrhage appeared occasionally when ultrasound-guided PMWA was used to treat cystic thyroid nodule, and interfered with treatment.…”
Section: Introductionmentioning
confidence: 93%
“…MWA is a new local thermal ablation technique that has a fast heating speed, strong coagulation ability, and a large ablation zone, so this technique has become a major method in heat ablation therapy. It is an effective treatment of thyroid nodules worldwide (8)(9)(10)(11). We found that intracystic hemorrhage appeared occasionally when ultrasound-guided PMWA was used to treat cystic thyroid nodule, and interfered with treatment.…”
Section: Introductionmentioning
confidence: 93%
“…High-quality evidence using MWA is limited. Retrospective studies describe a 74.6-90.0% mean volume reduction after 1 year [22], and in 2 meta-analyses volume reduction was 74% at 6 months and 89% at 12-month follow-up [65,66]. However, in a prospective study comparing the performance of cooled versus uncooled MWA applicators, the mean reduction rates at 3 months were only 40 and 29%, respectively [67].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…As with LTA and RFA, this variability in technique efficacy could be due to the heterogeneous structure of the nodules of the patients enrolled in the studies. Currently, MWA appears associated with a higher risk of major and minor complications than LTA and RFA, probably due to a poorer control of the applied energy and to the larger bore of the applicators [66].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…The VRRs of other minimally invasive techniques—RFA, LA, and MWA—are reported to be 76.1%, 49.9%, and 73.5, respectively, after six months (4,43). Although direct comparisons are limited by differences in the baseline characteristics of nodules, these findings indicate that RFA and MWA is somewhat more effective than HIFU, while LA is as effective as HIFU, for volume reduction after six months.…”
Section: Discussionmentioning
confidence: 99%